DOES LESS CORRUPTION REDUCE INCOME INEQUALITY IN INDONESIA? - Iskandar, Azwar (Badan Pemeriksa Keuangan Republik Indonesia, 2018)
It is widely believed that corruption is a cause of income inequality and a barrier to successful its eradication. It undermines the efforts of developing countries, including Indonesia to alleviate income inequality. It is also argued that the increased inequality caused by corruption worsens the position of the poorest people in a society as it reduces public resources available for social spen-ding of government. In addition, corruption might have a negative impact on the quality and quantity of public services, such as education and health services. This study designed to know the long run and short run impacts of corruption on inequality of income. The study uses secondary data from World Bank and Transparency International then Auto Regressive Distributed Lag (ARDL) and dynamic Error Correction Model (ECM) during the year of 1995-2017. The results of study indicate that corruption has significant effects on the level of income inequality both in the short and long run. The negative implication of corruption on citizens’ life is a major disaster in the economy and harmful to the growth and development of the people in Indonesian particularly, and the economy in general. The simple Pearson correlation findings also indicate that corruption has significant distributional consequences by affecting government expenditures. Therefore, the raise of corruption increases income inequality as it reduces the effectiveness of government spending on education, health and final consumption for society. Thus, it can be concluded that for the Indonesian context, an increased inequality due to corruption has worsened the position of the poorest as less resources available for social spending.